2009
DOI: 10.1111/j.1365-2095.2009.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin E supplementation on growth performance, lipid peroxidation and tissue fatty acid composition of black sea bream (Acanthopagrus schlegeli) fed oxidized fish oil

Abstract: A 9‐week feeding experiment was conducted to evaluate the effects of dietary vitamin E supplementation on growth, lipid peroxidation and fatty acid composition of black sea bream fed oxidized oil. The FL and OL diets contained fresh fish oil and oxidized oil, respectively, without additional vitamin E supplementation. Another four α‐tocopherol levels (150, 250, 450 and 800 mg kg−1 diet) were used within the OL diet, giving a total of six experimental diets. Fish were hand‐fed to apparent satiation twice daily.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
99
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 49 publications
15
99
2
3
Order By: Relevance
“…This effect of OFO on growth performance is disagreement with the findings in sea bream, Sparus aurata (Tocher et al 2003), Atlantic cod, (Zhong et al, 2008) and black sea bream, Spondyliosoma cantharus (Peng et al, 2009) fed different levels of oxidized oils for 8 weeks or more. Tocher et al (2003) reported that OFO slightly stimulated growth of sea bream for 8 weeks.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…This effect of OFO on growth performance is disagreement with the findings in sea bream, Sparus aurata (Tocher et al 2003), Atlantic cod, (Zhong et al, 2008) and black sea bream, Spondyliosoma cantharus (Peng et al, 2009) fed different levels of oxidized oils for 8 weeks or more. Tocher et al (2003) reported that OFO slightly stimulated growth of sea bream for 8 weeks.…”
Section: Discussioncontrasting
confidence: 52%
“…Decrease in whole-body crude protein content in black sea bream fed by OFO had been reported, while Vit. E abrogated this phenomena (Peng et al, 2009). Dietary GTE could lower lipid content of liver in flounder, Paralichthys olivaceus although the body lipid of the fish, without the livers, did not show any change in compare to control (Cho et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, it is very susceptible to oxidizing, and its oxidization results in formation of primary and secondary products such as lipid hydroperoxides, ketones and aldehydes. These oxidation products negatively affect feeds nutritive value and suppress fish growth (Huang & Huang, 2004;Peng et al, 2009). It has been reported that oxidized fish oil influences cholesterol metabolism leading to cholesterol shortage in cell (Ren & Huo, 2000).…”
Section: Discussionmentioning
confidence: 99%